1998
DOI: 10.1542/peds.102.5.e49
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Tuberculosis in Children: A Review of 214 Cases

Abstract: ABSTRACT. Objective. To study the clinical, laboratory, and treatment features observed in pediatric patients with tuberculous meningitis in Turkey.Study Design. Results. Of the 214 patients with tuberculous meningitis, 112 (52%) were male. The mean age at presentation was 4.1 years, with 165 patients (77%) younger than 5 years. Twenty-two patients (10%) were in the first stage of the disease, 120 (56%) in the second, and 72 (34%) in the third. Our epidemiologic data showed that 141 (66%) of the patients had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
8
20

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(138 citation statements)
references
References 22 publications
12
98
8
20
Order By: Relevance
“…One series of non-HIV-infected adult cases of CNS tuberculosis in Turkey found CSF lymphocyte predominance in 85%, neutrophil predominance in 15%, high protein levels in 77%, hypoglycorrachia in 67.2%, and elevated opening pressure in 54% of patients (Sutlas et al 2003). Similar results among a series of pediatric cases were also noted (Yaramis et al 1998), and coinfection with HIV does not appear to alter the CSF proûle (Thwaites et al 2005). Although hypoglycorrachia is common in both bacterial meningitis and TBM, its presence may provide a convenient discriminating feature that distinguishes these etiologies from most other causes of meningoencephalitis, especially when considering the initiation of empirical antibiotics.…”
Section: Cytologysupporting
confidence: 67%
“…One series of non-HIV-infected adult cases of CNS tuberculosis in Turkey found CSF lymphocyte predominance in 85%, neutrophil predominance in 15%, high protein levels in 77%, hypoglycorrachia in 67.2%, and elevated opening pressure in 54% of patients (Sutlas et al 2003). Similar results among a series of pediatric cases were also noted (Yaramis et al 1998), and coinfection with HIV does not appear to alter the CSF proûle (Thwaites et al 2005). Although hypoglycorrachia is common in both bacterial meningitis and TBM, its presence may provide a convenient discriminating feature that distinguishes these etiologies from most other causes of meningoencephalitis, especially when considering the initiation of empirical antibiotics.…”
Section: Cytologysupporting
confidence: 67%
“…Both children (56) and HIV-coinfected patients (14,52,169) are at high risk for developing CNS tuberculosis. Other risk factors include malnutrition and recent measles in children (246) and alcoholism, malignancies, and the use of immunosuppressive agents in adults (101,143,233). Studies conducted in developed countries have also identified that foreign-born individuals (individuals born outside of developed countries) are overrepresented among CNS tuberculosis cases (19,157).…”
Section: Epidemiologymentioning
confidence: 99%
“…Children with TBM often present with fever, stiff neck, seizures, and abdominal symptoms such as nausea and vomiting (57,246). Headache occurs less often than in adults.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…El conjunto de fenómenos patogénicos (vasculitis, isquemia, edema cerebral, granulomas e hidrocefalia) desencadenados a partir de la lesión tuberculosa son los responsables de los defectos motores, sensoriales y del intelecto que se manifiestan durante la evolución de estos pacientes. [5][6][7] Tal es el caso del paciente que presentamos, en quien las manifestaciones neurológicas no pueden explicarse exclusivamente por el compromiso meníngeo y la localización de los granulomas.…”
Section: Discussionunclassified